Numerical evaluation of thermal comfort using a large eddy lattice Boltzmann method. (April 2021) - Siodlaczek, Marc; Gaedtke, Maximilian; Simonis, Stephan; Schweiker, Marcel; Homma, Naohiko; Krause, Mathias J.
Abstract: Detailed numerical analyses of temperature and air velocity distributions are relevant to assess thermal comfort in a wide range of applications. Until now mainly simulations based on Reynolds-averaged Navier–Stokes equations (RANS) are used, whereby fluctuations as well as anisotropy of the turbulence are represented with insufficient precision. This paper applies a thermal large eddy lattice Boltzmann method (LES–LBM) as an efficient and accurate transient modeling of turbulence. The benchmark case Manikin Heat Loss for Thermal Comfort Evaluation is studied and the model of Predicted Mean Vote (PMV) is applied for estimating thermal sensation. The results for the air velocity, the temperature field and the PMV show a satisfactory agreement with both, the experiment and the results from RANS simulations. The accuracy and the model quality of the simulation are increased further by considering the buoyancy and an inlet seeding. This suggests a successful evaluation of the present model, whereby additional transient flow field data are provided. The obtained transient flow field data, however, motivates future work to study thermal comfort in the present manner. The investigation of the influence of fluctuations on thermal comfort as well as the application to more complex problems seem promising. Highlights: LES for transient incompressible thermal flow using a double distribution LBM. Validation with the benchmark case Manikin Heat Loss for Thermal Comfort Evaluation. PMV model applied to transient and time averaged data. LES–LBM results agree well with RANS and experimental reference data.